2018
DOI: 10.3389/fmicb.2018.00932
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin – Tigecycline Combination Shows Synergy Against Mycobacterium abscessus

Abstract: Lung disease caused by non-tuberculous mycobacteria (NTM), relatives of Mycobacterium tuberculosis, is increasing. M. abscessus is the most prevalent rapid growing NTM. This environmental pathogen is intrinsically resistant to most commonly used antibiotics, including anti-tuberculosis drugs. Current therapies take years to achieve cure, if cure if achieved. Thus, there is an urgent medical need to identify new, more efficacious treatments. Here, we explore the possibility of repurposing antibiotics developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Checkerboard titration assay. This assay was carried out in 96-well microtiter plates as previously described using optical density to assess growth [24]. Eight concentrations of CLR were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Checkerboard titration assay. This assay was carried out in 96-well microtiter plates as previously described using optical density to assess growth [24]. Eight concentrations of CLR were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Combinations of avibactam with each of the following drugs including ampicillin, amoxicillin, tebipenem, and panipenem displayed synergistic effects against M. abscessus. Furthermore, the carbapenems, tebipenem, and panipenem also exhibited synergy with a novel boronic acid β-lactamase inhibitor, vaborbactam ( Aziz et al, 2018 ). Thus, non-β-lactam-based β-lactamase inhibitors such as avibactam and vaborbactam can potentially extend the spectrum of β-lactams employed for the treatment of largely incurable, chronic M. abscessus pulmonary infections.…”
Section: Antibiotic-modifying Enzymes In M Abscessusmentioning
confidence: 99%
“…For example, vancomycin, an inhibitor of cell wall synthesis, exhibited synergy with clarithromycin, an inhibitor of protein synthesis, in M. abscessus ( Mukherjee et al, 2017 ). Likewise, a combination of tigecycline (which inhibits protein synthesis) with teicoplanin (which disrupts peptidoglycan synthesis) displayed a strong synergistic effect against M. abscessus ( Aziz et al, 2018 ). Since the mycobacterial cell envelope forms a major permeability barrier, drugs that perturb cell wall integrity, are likely to synergize with drugs having intracellular targets ( Le Run et al, 2018 ).…”
Section: Clinical Relevancementioning
confidence: 99%
“…As combination regimens are essential for clinical management of Mab infections, several studies have evaluated antibiotic synergy against Mab with mixed results (Cremades et al, 2009 ; Shen et al, 2010 ; Bastian et al, 2011 ; Choi et al, 2012 ; van Ingen et al, 2012 ; Oh et al, 2014 ; Singh et al, 2014 ; Ferro et al, 2016 ; Mukherjee et al, 2017 ; Aziz et al, 2018 ; Pryjma et al, 2018 ; Schwartz et al, 2018 ; Zhang et al, 2018 ). In vitro studies have shown variable synergy of β-lactams in combination with other drugs.…”
Section: Synergy Studies With β-Lactams and Other Drugsmentioning
confidence: 99%